2021
DOI: 10.1038/s42003-021-01696-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual excitation induces courtship ultrasonic vocalizations and cataplexy-like behavior in orexin neuron-ablated male mice

Abstract: Cataplexy is triggered by laughter in humans and palatable food in mice. To further evaluate mice’s cataplexy, we examined courtship behavior in orexin neuron-ablated mice (ORX-AB), one of the animal models of narcolepsy/cataplexy. Wild-type female mice were placed into the home cage of male ORX-AB and cataplexy-like behavior was observed along with ultrasonic vocalizations (USVs), also known as the “love song”. ORX-AB with a female encounter showed cataplexy-like behavior both during the dark and light period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…We backcrossed the mutant mice with C57BL/6 mice (Clea Japan Inc., Tokyo, Japan) for more than 10 generations. We have confirmed that the expression of orexin peptide disappeared in ORX-KO and ORX-abl mice [31,33]. cFos-tTA; TetO-GCaMP6 mice were generated by crossing Tg(Fos-tTA, Fos-EGFP*)1Mmay mice (obtained from The Jackson Laboratory, Stock No: 018306) with TetO-GCaMP6 knock-in mice (B6;129-Actb<tm3.1(tetO-GCaMP6)Kftnk >, obtained from the RIKEN Bio Resource Research Center, RBRC09552).…”
Section: Animalssupporting
confidence: 73%
See 1 more Smart Citation
“…We backcrossed the mutant mice with C57BL/6 mice (Clea Japan Inc., Tokyo, Japan) for more than 10 generations. We have confirmed that the expression of orexin peptide disappeared in ORX-KO and ORX-abl mice [31,33]. cFos-tTA; TetO-GCaMP6 mice were generated by crossing Tg(Fos-tTA, Fos-EGFP*)1Mmay mice (obtained from The Jackson Laboratory, Stock No: 018306) with TetO-GCaMP6 knock-in mice (B6;129-Actb<tm3.1(tetO-GCaMP6)Kftnk >, obtained from the RIKEN Bio Resource Research Center, RBRC09552).…”
Section: Animalssupporting
confidence: 73%
“…All animals were 8-16 weeks old at the start of each experiment. The generation of mutant mice has been described in detail elsewhere [28][29][30][31][32]. Regarding the method for selective ablation of orexin neurons (ORX-abl), orexintetracycline transactivator (tTA) mice, which express tTA exclusively in orexin neurons under the control of the human prepro-orexin promoter, were bred with tetO diphtheria toxin A fragment (DTA) mice (B6.Cg-Tg (tetO DTA) 1Gfi/J, The Jackson Laboratory) to generate orexin-tTA; tetO DTA mice.…”
Section: Animalsmentioning
confidence: 99%
“…We do not know whether such excitation, if any, might be enough to overcome succeeding inhibitory inputs to the orexin neurons. The second interpretation of the current results may be that the reduction of heart rate and GCaMP6 signals may indicate a transient slow-down of hyper arousal state with high sympathetic tones, because cataplexy often occurs in the middle of highly active behavior in ORX-deficient mice [ 2 , 20 , 21 ]. The lowered signals, especially the heart rate (~ 550 bpm, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin neurons express opioid receptors, and activation of the receptor inhibits orexin neuronal activity at least in vitro [ 28 ]. Positive emotions induce both cataplexy [ 21 , 29 ] and opioid release [ 30 ]. Sympathetic activation, a role of orexin neurons [ 31 ], is not as strong during negative emotions as during positive emotions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation